Materials Development by Additive Manufacturing Techniques - Fino, Paolo; Aversa, Alberta (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Additive manufacturing (AM) processes are gaining more and more attention from many industrial fields, mainly because they are revolutionizing the components' designs and production lines. The complete industrialization of these processes has to be supported by the full understanding of correlation between AM building conditions and the final materials' properties. Another critical aspect is that nowadays only a reduced number of materials processable by AM are available on the market. It is, therefore, fundamental to widen the materials' portfolio, and to study and develop new materials that can take advantage of these unique building processes.